Biginelli Reaction: Polymer Supported Catalytic Approaches - Patil, Rajendra V; Chavan, Jagdish U; Dalal, Dipak S; Shinde, Vaishali S; Beldar, Anil G (ACS combinatorial science, 2019)
The Biginelli product, dihydropyrimidinone (DHPM) core, and its derivatives are of immense biological importance. There are several methods reported as modifications to the original Biginelli reaction. Among them, many involve the use of different catalysts. Also, among the advancements that have been made to the Biginelli reaction, improvements in product yields, less hazardous reaction conditions, and simplified isolation of products from the reaction predominate. Recently, solid-phase synthetic protocols have attracted the research community for improved yields, simplified product purification, recyclability of the solid support, which forms a special economic approach for Biginelli reaction. The present Review highlights the role of polymer-supported catalysts in Biginelli reaction, which may involve organic, inorganic, or hybrid polymers as support for catalysts. A few of the schemes involve magnetically recoverable catalysts where work up provides green approach relative to traditional methods. Some research groups used polymer–catalyst nanocomposites and polymer-supported ionic liquids as catalyst. Solvent-free, an ultrasound or microwave-assisted Biginelli reactions with polymer-supported catalysts are also reported.